VLF/ELF Radiation from the Ionospheric Dynamo Current System Modulated by Powerful HF Signals - Ferraro, A J; Lee, H S; Allshouse, R; Carroll, K; Tomko, A A (1982)
This paper presents results of several compaigns at the Arecibo Observatory using the new HF high power heater facility. The specific measurement pertains to detecting VLF/ELF radiation from the ionospheric dynamo current system that has been periodically modified by pulsing the HF high power transmitter at VLF or ELF. Because of the nonlinear relationship between ionospheric conductivities and electron temperature, the high power HF source can produce modification of the ionospheric conductivities and consequently of the dynamo current system. That this effect indeed does occur is verified by detecting the VLF/ELF radiation from the current source. Most of the data presented in this paper are concerned with measurements made at ground level beneath the modified current region. Limited data are presented for ELF signals received in Pennsylvania, USA, over a long path from the HF heater facility at Tromsoe, Norway. Published in the Journal of Atmospheric and Terrestrial Physics, v44 n12 p1113-1122, 1982.